State Asset Utilization to Support Public Private Partnership Project in Indonesia: A State Asset Management Review - Surachman, Eko Nur (Yayasan Ilomata, 2024)
Public-Private Partnership (PPP) is one of the government strategies to provide infrastructure to serve the community. In the implementation process, PPP has challenges in land acquisition. In response to this challenge, the utilization of State Assets (Barang Milik Negara/BMN) in the form of land and buildings offers a prospective solution. To utilize the State Asset efficiently in the PPP scheme, the information on the asset should be updated based on the State Asset Management and Information System. This paper aims to describe the role of State Assets in supporting Public Private Partnership (PPP) projects in terms of achieving project financial feasibility using a particular study case and how to update the State Asset Management System. The methodology used in this paper uses qualitative methods with literature studies, focus group discussions (FGD), and interviews, to determine the intended role of State Assets. This paper shows that the existing asset management system has accommodated efforts to utilize state assets to support the PPP project. While from the information system point of view, the basic framework of the information system has been formed, the current project needs to be further developed referring to the basic framework of the information system so that it can effectively and efficiently support efforts to utilize state assets in PPP projects.